Evidence for a Dissociation Between Causal Beliefs and Instrumental Actions - Perez-Riveros, O (SAGE Publications Ltd, 2020)
Human experiments have demonstrated that instrumental performance of an action and the causal beliefs of the effectiveness of an action in producing a reward are correlated and controlled by the probability of an action leading to a reward. The animal literature, however, shows that instrumental performance under free-operant training differs even when the reward probabilities are matched while subjects undergo training under ratio or interval schedules of reward. In two experiments, we investigated whether causal beliefs would correlate with instrumental performance under ratio and interval schedules for matched reward probabilities. In both experiments, we found that performance was higher under ratio than under interval training. However, causal beliefs were similar between these two conditions despite these differences in instrumental performance. When reward probabilities were increased by experimental manipulations in Experiment 2, the causal beliefs increased but performance decreased with respect to Experiment 1. This is evidence that instrumental performance and causal action-reward attribution may not follow from the same psychological process under free-operant training. © Experimental Psychology Society 2020.